2018
DOI: 10.3892/etm.2018.6394
|View full text |Cite
|
Sign up to set email alerts
|

Expression of miR‑376 in blood of pregnant women with preeclampsia and its effect on 25‑hydroxyvitamin D

Abstract: The study aims to investigate the clinical significance of regulating the expression of 25-hydroxyvitamin D (25-OH-VD) via microRNA (miRNA)-376c in the occurrence and development of preeclampsia (PE) in pregnant women. Peripheral blood and placental tissues were collected from pregnant women in 4 groups, including 67 normal pregnant women, 41 pregnant women with gestational hypertension, 40 pregnant women with mild PE and 51 pregnant women with severe PE. The expression of 25-OH-VD and miRNA-376c in peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Moreover, Baker et al described the miRNA‐376c expression is low in PE. With progression of disease, this miRNA expression was elevated, suggesting that the dysregulation of miRNA‐376c and 25‐OH‐VD mRNA was remarkably associated with urine protein and blood pressure in pregnant women and demonstrated that 25‐OH‐VD and miRNA‐376c interact with each other and involved in progression and occurrence of hypertensive disorder complicating pregnancy such as PE. By examining the placenta samples, there have been proven expressions of some miRNAs such as miR‐149, miR‐194, miR‐260‐5p, miR‐103a‐3p, miR‐145‐5p, miR‐16‐5p, miR‐100‐5p, and miR‐221‐3p downregulated in PE .…”
Section: Epigenetic Changes In Pementioning
confidence: 99%
“…Moreover, Baker et al described the miRNA‐376c expression is low in PE. With progression of disease, this miRNA expression was elevated, suggesting that the dysregulation of miRNA‐376c and 25‐OH‐VD mRNA was remarkably associated with urine protein and blood pressure in pregnant women and demonstrated that 25‐OH‐VD and miRNA‐376c interact with each other and involved in progression and occurrence of hypertensive disorder complicating pregnancy such as PE. By examining the placenta samples, there have been proven expressions of some miRNAs such as miR‐149, miR‐194, miR‐260‐5p, miR‐103a‐3p, miR‐145‐5p, miR‐16‐5p, miR‐100‐5p, and miR‐221‐3p downregulated in PE .…”
Section: Epigenetic Changes In Pementioning
confidence: 99%
“… [ 18 23 ] miR-182-5p placenta upregulated RND3 the increased miRNA-182-5p expression could inhibit the migratory and invasive ability of trophoblast cells through targeted degrading RND3 protein [ 24 ] miR-155 placenta/placenta-associated serum exosomes upregulated CYR61/Cyclin D1 Overexpression of miR-155 in HTR-8/SVneo cells inhibited cell invasion, proliferation and increased cell number at the G1 stage in trophoblast cells [ 16 , 25 ] miR-155-5p placenta upregulated eNOS miR-155 inhibited cell invasion in trophoblast cells, and the effect was rescued by over expression of eNOS. [ 26 ] miR-195 placenta downregulated ActRIIB/ActRIIA miR-195 could promote cell invasion via directly targeting ActRIIB/ActRIIA in human trophoblast cells [ 27 ] miR-16 placenta/mesenchymal stem cell (MSC) upregulated CCNE1 /VEGF-A/Notch2 over-expressed miR-16 inhibited the proliferation and migration of decidua-derived mesenchymal stem cells /BeWo and JEG-3 cells, and induced cell-cycle arrest by targeting cyclin E1 [ 28 , 29 ] miRNA-376c placenta/plasma/exosome downregulated ALK5/ALK7/25-OH-VD miR-376c inhibits both ALK5 and ALK7 expression to impair transforming growth factor-β/Nodal signaling, leading to increases in cell proliferation and invasion [ 30 , 31 ] miR-29b decidua-derived mesenchymal stem cell (dMSC)/placenta upregulated MMP2/MCL1/ VEGFA/ ITGB1/HDAC4 miR-29b induced apoptosis and inhibited invasion and angiogenesis of trophoblast cells. [ 32 ] miR-101 placenta downregulated ERp44/BRD4/CXCL6 miR-101 could promote apoptosis and inhibite the proliferation and migration of...…”
Section: Mirnas and Preeclampsiamentioning
confidence: 99%
“…25 Furthermore, a study has suggested the existence of a potential correlation between miRNAs associated with PE and vitamin D (25OHD) levels in the placenta, which may be reflected in peripheral blood. 26 Accordingly, the primary aim of this study is to identify circulating miRNAs associated with subclinical PE during early stages of pregnancy (10-18 weeks of gestation) and to discover the target genes that these DE miRNAs regulated within the PE-related disease module, that is, DE transcriptome signatures during the same gestational period. For this investigation, we used the same VDAART nested case-control cohort that was used for the prior whole blood gene expression study and construction of the PE-related disease module.…”
Section: Introductionmentioning
confidence: 99%
“…The potential impact of vitamin D intake on the expression of several circulating miRNAs has been demonstrated in healthy status 25 . Furthermore, a study has suggested the existence of a potential correlation between miRNAs associated with PE and vitamin D (25OHD) levels in the placenta, which may be reflected in peripheral blood 26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation